Buckling analysis of column with trapezoid web - Osman, Mohd. Hanim (Penerbit UTM, 2008)
Trapezoidal web section is a type of flanged stee l section with the web part made corrugated in trapezoidal form (Fig. 4.1). Plate girders fabricated from TWP s ection offer an alternative to conventional hot rolled and welded sections of uniform web profile. They have been proven to be more economical in terms of materials us ed and the time of fabrication [1]. Study on trapezoid web girder sections has been conducte d in the Steel Technology Centre, Universiti Teknologi Malaysia to develop a design guide for beam with trapezoid web profile. For compression member, a comprehensive analytical a nd experimental study is required to complete the design guide. There is no evidence of research effort in this subject. The objective of this research is to develop th e formulation for the buckling capacity of column with trapezoid web. The scope of the study is focused on the comparison of lateral bending behavior between flat web (FW) and TWP section to study the effect of corrugated profile on the second moment of area (I) of the section, by experi mental, analytical and numerical approaches. It was followed by the study on buck ling load using eigenvalue an alysis in the LUSAS finite element program. The deflection and buck ling study was for the minor axis only.